Factors Associated With Participation in the Chronic Disease Self-Management Program: Findings From the SUCCEED Trial. Issue 10 (October 2020) - Lin, Amy M.; Vickrey, Barbara G.; Barry, Frances; Lee, Martin L.; Ayala-Rivera, Monica; Cheng, Eric; Montoya, Ana V.; Mojarro-Huang, Elizabeth; Gomez, Patricia; Castro, Marissa; Corrales, Marilyn; Sivers-Teixeira, Theresa; et al.
Abstract : Background and Purpose: Self-management programs may improve quality of life and self-efficacy for stroke survivors, but participation is low. In a randomized controlled trial of a complex, multidisciplinary, team-based secondary stroke prevention intervention, we offered participants Chronic Disease Self-Management Program (CDSMP) workshops in addition to clinic visits and home visits. To enhance participation, workshops were facilitated by community health workers who were culturally and linguistically concordant with most participants and scheduled CDSMP sessions at convenient venues and times. Over time, we implemented additional strategies such as free transportation and financial incentives. In this study, we aimed to determine factors associated with CDSMP participation and attendance. Methods: From 2014 to 2018, 18 CDSMP workshop series were offered to 241 English and Spanish-speaking individuals (age ≥40 years) with recent stroke or transient ischemic attack. Zero-inflated Poisson regression was used to identify factors associated with participation and attendance (ie, number of sessions attended) in CDSMP. Missing values were imputed using multiple imputation methods. Results: Nearly one-third (29%) of intervention subjects participated in CDSMP. Moderate disability and more clinic/home visits were associated with participation. Participants with higher numbers of clinic and home visits (incidence rate ratio [IRR], 1.06 [95% CI, 1.01–1.12]), severe (IRR, 2.34 [95% CI, 1.65–3.31]), and moderately severe disability (IRR, 1.55 [95% CI, 1.07–2.23]), and who enrolled later in the study (IRR, 1.12 [95% CI, 1.08–1.16]) attended more sessions. Individuals with higher chaos scores attended fewer sessions (IRR, 0.97 [95% CI, 0.95–0.99]). Conclusions: Less than one-third of subjects enrolled in the SUCCEED (Secondary Stroke Prevention by Uniting Community and Chronic Care Model Teams Early to End Disparities) intervention participated in CDSMP; however, participation improved as transportation and financial barriers were addressed. Strategies to address social determinants of health contributing to chaos and engage individuals in healthcare may facilitate attendance. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01763203. Abstract : Supplemental Digital Content is available in the text.